THE IMPLEMENTATION OF SHADOWING TECHNIQUE TO IMPROVE STUDENTS’ LISTENING ABILITY AT TOEFL PREPARATION CLASS - Asis Warni; Allen Christy Jufri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The research is aimed to figure out the effect of implementating shadowing technique to improve students’ listening ability at TOEFL Preparation class of University Sumatera Barat. The research was conducted on October 1st to November 26th, 2025 at the TOEFL preparation class of Nursing Department. They were 22 students enrolled the class and all of them were taken as the sample by applying total sampling technique. The treatment was done in eight meetings all together included pre-test and post-test. The experimental research design was employed in getting the data of the research. The data taken by listening test, the test was divided into pre-test and post-test. The data analysis was conducted by using the T-test formula. The result of t-Test was (-7,115) with df 21 and significance 0.000. The significant score of the research 0.148. It was greater than significant level 0.05. It means that the implementation of shadowing techniques significantly improve the students’ listening ability at TOEFL preparation class.Keywords: Shadowing Technique, Listening Ability, TOEFL